Consumption effect of a synbiotic beverage made from soy and yacon extracts containing Bifidobacterium animalis ssp lactis BB-12 on the intestinal polyamine concentrations in elderly individuals - Jovenasso Manzoni, Marla Simone [UNESP]; Rossi, Elizeu Antonio [UNESP]; Pauly-Silveira, Nadiege Dourado [UNESP]; Pinto, Roseli Aparecida [UNESP]; Roselino, Mariana Nougalli [UNESP]; Carlos, Iracilda Zeppone [UNESP]; Quilles, Marcela Bassi [UNESP]; Abreu Gloria, Maria Beatriz de; Umbelino Cavallini, Daniela Cardoso [UNESP] (Elsevier B.V., 2017)
This study aimed to investigate the effect of a synbiotic beverage made from soy and yacon (Smallanthus sonchifolius) extracts containing Bifidobacterium animalis ssp. lactis BB-12 on healthy elderly individuals' intestinal polyamine concentrations. A randomized, double-blinded, placebo-controlled trial has been conducted with twenty-nine volunteers (over 65 years of age) who either had a daily intake of 150 mL of synbiotic (synbiotic group - S) or placebo (placebo group - P) beverages. Both had the same nutrient composition, except that a probiotic culture was added to the synbiotic beverage. Total experiment time was 8 weeks, which was divided into 3 consecutive phases: a prefeeding period (2 weeks), followed by a feeding period (4 weeks) and a postfeeding period (2 weeks). Stool samples were collected at 3 time periods. Fecal concentrations of poly amines, putrescine (PUT), cadaverine (CAD) and spermidine (SPD) that were obtained during the synbiotic and placebo consumption period were significantly higher (p < 0.05) than those found during the pre-consumption baseline level period. No significant differences in the number of bifidobacteria, clostridia, or enterobacteria were observed in any of the two groups at the three time periods. Similarly, no significant effect on the production of proinflammatory cytokines tumor necrosis factor-alpha (TNF-alpha), interleukin-6 (IL-6) and anti-inflammatory interleulcin-10 (IL-10) was induced by the synbiotic or placebo beverages consumption. The results herein indicate that both the synbiotic and the placebo beverage consumption have increased polyamines levels, which are often reduced in elderly individuals, without influencing inflammatory responses. In addition, both placebo and synbiotic beverages seems to contribute by maintaining increased polyamines levels.
Keywords: Soy; Yacon; Bifidobacterium; Polyamine; Gut environment; Elderly